PERAN GENDER DALAM MEMODERASI PENGARUH DISKONFIRMASI POSITIF, PERCEIVED VALUE, DAN KEPERCAYAAN TERHADAP NIAT PEMBELIAN ULANG DARING - Effed darta Hadi; Akram Harmoni Wiardi (The Manager Review, 2019)
The purpose of the study is to examine empirically the role of gender as a moderating effect  of positive disconfirmation, trust, and perceived value towards the intention to repurchase. This research is a quantitative research and confirmatory which is to examine the cause and effect relationship between variables in this study based on previous research tests with different place settings and research samples. The method in this study is the survey method, the sample of the study respondents in this study are consumers who have done transactions through online buying and selling sites. The stages in this study include; preparation of research proposals, conducting surveys, data processing, data interpretation, and preparation of research reports. The results of this study are expected to provide practical and theoretical contributions regarding consumer behavior.